Unlocking the potential of social learning for climate change and food security: Wicked problems and non-traditional solutions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Climate change is a crisis not only because of its vast global impact, but because it is so difficult to do much about it. Four degrees of warming are projected for this century under a business-as-usual scenario. In agriculture, this would mean the end of farming as we know it in the developing world. But to adapt agriculture, ensure food security and prevent deepening poverty, we must deal with a highly complex socio-ecological system whose mechanisms and effects are uncertain. Constraints and challenges evolve over time and are altered every time people change the ways they produce food.